Decay Properties of Global Solutions for Benjamin-Ono Equation of High Order (Journal of Partial Differential Equations, 1995)
The decay properties of global solutions for the Benjamin-Ono equation of high order are obtained as |x| → ∞. An Iorio's type result is derived for this equation.